Izbočitev krožnega kolobarja v elastoplastičnem področju: elastičen linearno utrjevalni reološki model - Bremec, Boštjan (Strojniški vestnik, 2001)
This paper treats the buckling problem of a circular annular plate where the unstable state and the buckling process occur when the stress state at the most loaded points of the plate is already in the elastic-plastic region. We analysed the cases with axisymmetric loads, the stress state and the supports of the plate. The outer and inner edges of the annulus were supported (clamped or simply supported) or free and loaded with constant pressures pn and pz in an arbitrary ratio. With the use of the equillibrium method the buckling loads were calculated for different ratia of the inner and outer radii a/b. It is supposed that the plate buckles axisymmetrically (sphericaly m=0) or non-axiasymmetrically with m>0 waves in the circumferential direction. The results show the influence of the material-hardening coefficient f on the buckling load. A comparison between calculations with a consideration of finite and incremental stress-strain relations is given.
Keywords: kolobarji krožni; procesi izbočitve; področja elastoplastična; modeli reološki; krožni kolobar; reologija; elastičnost; plastičnost; deformacija; modeli